A Confirmatory Factor Analysis of Facets of Psychological Flexibility in a Sample of People Seeking Treatment for Chronic Pain. Issue 2 (25th November 2015) - Scott, Whitney; McCracken, Lance M.; Norton, Sam
Abstract: Background: Evidence supports the validity of individual components of the psychological flexibility model in the context of chronic pain. However, there is a need to test the inter-relationships amongst measures of individual components of psychological flexibility in a more integrative manner. In particular, research is needed to examine whether a model with discrete facets as proposed is indeed reflected in data from currently used assessment measures in people with chronic pain. Purpose: This cross-sectional study investigated the underlying structure of measures of processes of psychological flexibility amongst individuals with chronic pain and the associations between this measurement model and patient functioning. Methods: Five-hundred and seventy-three adults with chronic pain completed measures of pain, physical and social functioning, mental health, depression and processes of psychological flexibility, including acceptance, cognitive defusion, decentering and committed action. Confirmatory factor analyses tested lower-order, higher-order and bifactor models to examine the structure of psychological flexibility process measures. Results: A single general factor reflecting openness explained variability in items across all of the psychological flexibility process measures. In addition to this general factor, distinct decentering and committed action group factors emerged in the data. As expected, the general factor was strongly correlated with measures of social functioning, mental health and depression. Conclusions: Future research is needed to determine the most useful means by which the presence of the general factor can be reflected in the measurement and theory of psychological flexibility.